Serum beta human chorionic gonadotropin and lipid profile in early second trimester (14-20 weeks) is a predictor of pregnancy-induced hypertension - Soundararajan, Pradeeba; Muthuramu, Poovathi; Veerapandi, Munira; Mariyappan, Rubini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: A variety of biological, biochemical, and biophysical markers implicated in the pathophysiology of pre-eclampsia during the last two decades have instigated the growing interest in this study to include both βhCG and lipid profile studies in the early second trimester as early predictors of pregnancy-induced hypertension. Early identification of at-risk women may help in taking timely preventive and curative management to prevent or delay complications associated with pregnancy-induced hypertension. Methods: A prospective study was performed on 100 patients attending the outpatient department of the Obstetrics and Gynaecology of the Raja Mirasudar hospital. All the patients were screened for serum βhCG and serum lipid profile in their early second trimester (14-20 weeks) and followed up till their delivery. Comparative studies of serum βhCG and serum lipid profile were performed between those who remain normotensive (group I) and those who developed pregnancy-induced hypertension (group II). Results: TG, HDL, VLDL, and LDL and BETA HCG values for those women who developed PIH (group II) were significantly higher than those who remain normotensive (group I), with p value of <0.01 which is statistically significant. HDL and βhCG values for group II were not higher than those in group I with p value >0.05 which is statistically insignificant. Conclusions: Maternal lipid profile and BETA HCG in second trimester is very good noninvasive test which can be used for prediction of pregnancy-induced hypertension before its clinical onset.